2016
DOI: 10.1371/journal.pgen.1005984
|View full text |Cite
|
Sign up to set email alerts
|

Control of Neural Daughter Cell Proliferation by Multi-level Notch/Su(H)/E(spl)-HLH Signaling

Abstract: The Notch pathway controls proliferation during development and in adulthood, and is frequently affected in many disorders. However, the genetic sensitivity and multi-layered transcriptional properties of the Notch pathway has made its molecular decoding challenging. Here, we address the complexity of Notch signaling with respect to proliferation, using the developing Drosophila CNS as model. We find that a Notch/Su(H)/E(spl)-HLH cascade specifically controls daughter, but not progenitor proliferation. Additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
47
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 85 publications
6
47
0
Order By: Relevance
“…We analyzed mutants in the kuz gene, which encodes an ADAM metalloprotease crucial for cleavage of the Notch receptor (Pan and Rubin, 1997;Sotillos et al, 1997), that have been demonstrated to reduce Notch signaling without affecting NB selection (Ulvklo et al, 2012;Bivik et al, 2016). However, we did not observe any apparent reduction in Seq protein levels in kuz mutants (Fig.…”
Section: Seq Interacts With the Notch Signaling Pathwaymentioning
confidence: 73%
See 4 more Smart Citations
“…We analyzed mutants in the kuz gene, which encodes an ADAM metalloprotease crucial for cleavage of the Notch receptor (Pan and Rubin, 1997;Sotillos et al, 1997), that have been demonstrated to reduce Notch signaling without affecting NB selection (Ulvklo et al, 2012;Bivik et al, 2016). However, we did not observe any apparent reduction in Seq protein levels in kuz mutants (Fig.…”
Section: Seq Interacts With the Notch Signaling Pathwaymentioning
confidence: 73%
“…These regulators exert their roles by regulating the key cell cycle genes (Baumgardt et al, 2014). In addition, the canonical Notch pathway was also found to be important for the type I>0 switch, via regulation of all four key cell cycle genes (Ulvklo et al, 2012;Bivik et al, 2015Bivik et al, , 2016. Notch signaling is initially off in NBs -a prerequisite for establishment of NB cell identity in the neuroectoderm -but is gradually activated during lineage progression (Ulvklo et al, 2012;Bivik et al, 2016).…”
Section: /P27mentioning
confidence: 99%
See 3 more Smart Citations